Impact of Different Nanoparticles on Common Wheat (Triticum aestivum L.) Plants, Course, and Intensity of Photosynthesis - Lauris Jankovskis; Inese Kokina; Ilona Plaksenkova; Marija Jermaļonoka (The Scientific World Journal)
The size of nanoparticles (NPs) allows them to accumulate in plants, and they affect plant growth by altering the size of leaves and roots and affecting their photosynthetic reactions by altering the composition of proteins in the electron transport chain, chlorophyll biosynthesis, and carbohydrate synthesis reactions. Plants play an important role on Earth as nutrient producers in all trophic food webs by producing oxygen, absorbing carbon dioxide, and synthesizing edible carbohydrates during photosynthesis. In this study, Fe3O4 and ZnO NPs at various concentrations (0, 1, 2, and 4 mg/l) were used to investigate the effect of NPs on plant morphological parameters and photosynthesis intensity, determining the amount of chlorophyll and the absorption of their light spectrum in common wheat (Triticum aestivum L.). Fe3O4 (25 nm, 2 mg/l, and 4 mg/l) and ZnO (32 nm, 4 mg/l) significantly increased the leaf length of common wheat seedlings. However, Fe3O4 NPs (25 nm, 1 mg/l, and 4 mg/l) significantly reduced light absorption at 645 and 663 nm and the content of chlorophyll b, chlorophyll a, and total chlorophyll, but Fe3O4 (25 nm, 2 mg/l) significantly reduced the chlorophyll a content. In addition, ZnO NPs (32 nm, 1 mg/l) significantly increased the chlorophyll b content. This study has made a major contribution to understanding the effect of low concentrations of NPs on plant seedlings. Currently, NPs with high concentrations, starting at 10 mg/l, have been analysed in other studies, but in the environment, NPs enter plants in low concentrations as dust or through water droplets. Therefore, it is important to determine the potential impact of small concentrations of NPs on crops that are important for agriculture.